Between food growing and leisure: contemporary allotment gardeners in Western Germany and Poland - Maćkiewicz, Barbara; Szczepańska, Magdalena; Kacprzak, Ewa; Fox-Kämper, Runrid (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
Allotment gardens have existed in Europe for 170 years and have changed their functions over time. While the scholarly literature emphasizes the economic, social and ecological benefits of allotment gardens, little is known about today’s allotment gardeners, especially in different geopolitical environments. This paper describes allotment gardeners’ profiles based on empirical data obtained from surveys conducted in two countries with, on the one hand, a long tradition of allotment gardens and, on the other hand, a recent history of belonging to two different geopolitical regions: Poland and West Germany. Inspired by the cultural-geographical approach that acknowledges that the gardening practice is influenced by culture and based on the method of non-hierarchical “k-means” clustering, this paper identifies characteristics of today’s allotment gardeners from the region of Westphalia-Lippe in Germany and of Wielkopolska in Poland. Significant differences in profiles were factored together in the statistical analysis based on garden practices and the meanings attributed to these practices as reported by the gardeners in the survey. As a result, German gardeners can be described first and foremost as urban farmers and ecologists, while Polish allotmenteers seem to prefer using their gardens for leisure (as well as a holiday retreat) and for ornamental purposes. Results can inform municipalities, stakeholders and garden organizations who are interested in adjusting existing allotment garden areas to meet future needs. However, in both countries the community of gardeners cannot be conclusively defined, as it is subject to further development, triggered by a generational change in many allotment gardens. For instance, in the context of the recent COVID-19 crisis, a significant increase in demand for allotment plots has been reported in both countries, which again confirms their role in times of crisis.